2021
DOI: 10.1111/apt.16377
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short‐ and long‐term effectiveness between ustekinumab and vedolizumab in patients with Crohn's disease refractory to anti‐tumour necrosis factor therapy

Abstract: Summary Background The best option between vedolizumab and ustekinumab after anti‐tumour necrosis factor (TNF) failure remains unclear in Crohn's disease. Aims To compare the short‐ and long‐term effectiveness of vedolizumab and ustekinumab in Crohn's disease patients with prior anti‐TNF exposure. Methods All Crohn's disease patients treated with ustekinumab or vedolizumab after exposure to at least one anti‐TNF agent were included from two referral centres. Primary endpoint was corticosteroid‐free clinical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 30 publications
4
37
1
Order By: Relevance
“…We found ustekinumab to be superior in inducing remission, while no difference was noticed between ustekinumab and vedolizumab at 52 weeks. This finding is in contrast with three previously published propensity score‐matched analyses including 45 (Liverpool study), 24 85 and 224 (two French studies), 26 , 41 and 107 (Dutch study) 25 ustekinumab‐treated CD patients, respectively, in which they found (although with some important differences), ustekinumab to be superior in maintaining remission at 1‐year follow‐up. There might be a number of reasons for this apparent discrepancy, and one reason is that propensity score‐matched analysis may underperform when the number of included patients is low, increasing the risk of overfitting.…”
Section: Discussioncontrasting
confidence: 99%
“…We found ustekinumab to be superior in inducing remission, while no difference was noticed between ustekinumab and vedolizumab at 52 weeks. This finding is in contrast with three previously published propensity score‐matched analyses including 45 (Liverpool study), 24 85 and 224 (two French studies), 26 , 41 and 107 (Dutch study) 25 ustekinumab‐treated CD patients, respectively, in which they found (although with some important differences), ustekinumab to be superior in maintaining remission at 1‐year follow‐up. There might be a number of reasons for this apparent discrepancy, and one reason is that propensity score‐matched analysis may underperform when the number of included patients is low, increasing the risk of overfitting.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 63 studies (including 8529 patients) met the inclusion criteria and were finally included in the systematic review and meta-analysis ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Predictors of response were reported in 37 studies (59%). The most frequent predictors of poor clinical response were previous biologic exposure (anti-TNF and/or vedolizumab) [ 26 , 39 , 40 , 44 , 47 , 51 , 65 , 72 , 74 ], stricturing disease [ 19 , 20 , 39 , 44 , 65 ], penetrating disease [ 27 , 39 , 44 , 51 , 65 ], and high Harvey-Bradshaw index (HBI) at first dose [ 19 , 20 , 51 , 72 , 73 , 75 ]. Concomitant corticosteroids, extraintestinal manifestations, male sex, old age, smoking, and low body mass index were also reported in some studies.…”
Section: Resultsmentioning
confidence: 99%
“…Manlay et al [94] compared the short-and long-term effectiveness of vedolizumab and ustekinumab in CD patients with prior anti-TNF exposure. After propensity score analysis (ensuring that prior primary anti-TNF non-response was similar for both groups), ustekinumab was more effective than vedolizumab to achieve corticosteroid-free clinical remission at Week 54 (49% vs. 41%) and deep remission at Week 14 (26% vs. 3.8%).…”
Section: Comparison Between Vedolizumab and Ustekinumab Treatment In Anti-tnf Experienced Patientsmentioning
confidence: 99%